Pengaruh Komitmen Organisasi, Remunerasi Dan Pengembangan Karir Terhadap Kinerja Melalui Motivasi Pegawai Pada Badan Urusan Administrasi Mahkamah Agung RI - Rizqi Widi Feirdani; Moh. Sutoro; N. Lilis Suryani (Jurnal Ekonomi dan Bisnis Digital, 2025)
The purpose of this study is to identify, analyze, and empirically test the influence of organizational commitment, remuneration, and career development on employee performance through employee motivation. The research was conducted using quantitative descriptive methods. The sampling technique used the Slovin method which amounted to 205 respondents. The data used in this study are primary data collected through questionnaires. Data analysis using structural equation modeling (SEM) with partial least square (PLS) method with the help of SmartPLS 3.2.9 program. The results of the study can be concluded as follows: Organizational commitment has a positive and significant effect on employee motivation. Remuneration has a positive and significant effect on employee motivation. Career development has a positive and significant effect on employee motivation. Organizational commitment has a positive and significant effect on employee performance. Remuneration has a positive and significant effect on employee performance. Career development has a positive and significant effect on employee performance. Employee motivation has a positive and significant effect on employee performance. Organizational commitment has a positive and significant effect on employee performance through work motivation. Remuneration has a positive and significant effect on employee performance through work motivation. Career development has a positive and significant effect on employee performance through work motivation.